Genetic dissection of thousand-seed weight in linseed (Linum usitatissimum L.) using multi-locus genome-wide association study - Saroha, Ankit; Gomashe, Sunil S.; Kaur, Vikender; Pal, Deepa; Ujjainwal, Shraddha; Aravind, J.; Singh, Mamta; Rajkumar, S.; Singh, Kuldeep; Kumar, Ashok; Wankhede, Dhammaprakash Pandhari (Frontiers in Plant Science, 2023)
Flaxseed/linseed is an important oilseed crop having applications in the food, nutraceutical, and paint industry. Seed weight is one of the most crucial determinants of seed yield in linseed. Here, quantitative trait nucleotides (QTNs) associated with thousand-seed weight (TSW) have been identified using Multi-locus Genome Wide Association Study (ML-GWAS). Field evaluation was carried out in five environments in multi-year-location trials. SNP genotyping information of the AM panel of 131 accessions comprising 68,925 SNPs were employed for ML-GWAS. From the six ML-GWAS methods employed, five methods helped identify total 84 unique significant QTNs for TSW. QTNs identified in ≥2 methods/environments were designated as stable QTNs. Accordingly, 30 stable QTNs have been identified for TSW accounting up to 38.65% trait variation. Alleles with positive effect on trait were analyzed for 12 strong QTNs with r2 ≥ 10.00% which showed significant association of specific alleles with higher trait value in three or more environments. Total 23 candidate genes have been identified for TSW, which included B3 domain-containing transcription factor, SUMO-activating enzyme, protein SCARECROW, shaggy-related protein kinase/BIN2, ANTIAUXIN-RESISTANT 3, RING-type E3 ubiquitin transferase E4, auxin response factors, WRKY transcription factor, and CBS domain-containing protein. In silico expression analysis of candidate genes was performed to validate their possible role in different stages of seed development process. The results from this study provide significant insight and elevate our understanding on genetic architecture of TSW trait in linseed